Anti-CD137 agonist antibody–independent and clinically feasible preparation of tumor-infiltrating lymphocytes from soft tissue sarcoma and osteosarcoma - Jin, Yining; Jia, Zhiliang; Xia, Xueqing; Gordon, Nancy B.; Ludwig, Joseph A.; Somaiah, Neeta; Li, Shulin (Frontiers in Immunology, 2025)
BackgroundTumor infiltrating lymphocytes (TILs) therapy has been proved for treatment of metastatic melanoma and is under investigation for other types of solid tumors. However, these successes are threatened by discontinued supply of GMP-grade anti-CD137 agonist, a key TIL preparation reagent. Therefore, exploring a GMP-adherent method for expanding endogenous TILs without anti-CD137 agonist is urgent. Toward this end, we aimed to establish an anti-CD137–independent and clinically feasible TIL expansion protocol to prepare TILs from under investigated sarcoma tumors.MethodsWe collected resected tumors from patients and cut tissues into fragments. We used IL-2 and T-cell activator CD3/CD28 without anti-CD137 agonist to expand nonselected TILs in 2-3 weeks, then rapidly expanded them over 2 weeks. Their phenotypes were characterized using flow cytometry. Their antitumor activity was validated in vitro using cytotoxic T lymphocyte assays measuring CD107a on the TILs and the viability of tumor cells and in vivo using an autologous patient-derived xenograft (PDX) tumor model.ResultsWe successfully expanded TILs in > 90% of collected samples. TILs generated preferentially increased CD8+ T cells but suppressed CD4+ T cells. A small portion of TILs were resident memory T cells. The expanded TILs reduced autologous tumor cells by 37.5% within 24 hours. Infusion of TILs in mice bearing autologous PDX tumors strongly inhibited liposarcoma growth. FDA has approved use of this GMP-feasible protocol in our clinical trial (IND 30562).ConclusionIt is feasible to generate antitumor TILs using CD3/CD28 activator to replace the unavailable anti-CD137 agonist. Our study supports the further development of TIL-based therapy.